The impact of renewable generation on system locational marginal price and total system losses - Yang K.; Tan C.S.; Garba A.; Lo K.L. (Muk Publications and Distributions, 2023)
Wind generation is one of the most mature and cost-effective resources among different types of the renewable energy technology. Large-scale wind generation projects have been commissioned around the world and are much more coming on stream in the nearest future. Because of its high degree intermittency, its effect on system operation needs to be investigated especially in a market environment. One of the key elements for investigation is the cost aspect of energy in a power system with increasing penetration of wind generation. This paper investigates the impacts of wind generation on system locational marginal price and total system losses considering different penetration levels and dispersion of wind generation in the network. 2018, Muk Publications and Distributions. All rights reserved.